Hose-drawn traveler with a line of sprinklers, an alternative to the gun-sprinkler traveller system. - Silva, Luis Leopoldo (2009)
Traveling sprinkler systems usually use a large volume gun-sprinkler that requires high operating pressures. These sprinklers deliver water at high application rates with large drops that can damage some plants and can also destroy soil surface structure, in some cases leading to surface sealing which reduces soil infiltration causing runoff. They can also be characterized for having low uniformity applications, especially in windy areas. The use of a line with medium or low-pressure sprinklers, mounted in the system-moving vehicle, instead of the gun-sprinkler, can be an alternative to the use of traveler systems in some crops and topographic conditions. The smaller sprinklers require less operating pressure, apply water with smaller drops and their overlapping can increase the irrigation uniformity. Field tests were made to evaluate the performance of the traveler machine with a line of four sprinklers (250 kPa) and a gun-sprinkler (350 kPa), with three different travel speeds, corresponding to three different application depths, and different wind speeds. In windy conditions, with wind speeds between 1,4 and 4,0 m/s, and a single pass, the irrigation events with the line of sprinklers produced more uniform irrigation events, especially in the low quarter, than the gun-sprinkler. Evaporation and wind drift losses were slightly higher with the line of sprinklers, although these events had higher potential application efficiency. The systems performance can be increased with the overlapping of the irrigated strips, with similar increments for both system options.